2001
DOI: 10.1016/s0893-133x(00)00199-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of MDMA (Ecstasy) on Prepulse Inhibition and Habituation of Startle in Humans after Pretreatment with Citalopram, Haloperidol, or Ketanserin

Abstract: Prepulse inhibition (PPI) of the acoustic startle response is : 3, MDMA; Ecstasy; Serotonin; Citalopram; Haloperidol; Ketanserin; Human; Prepulse inhibition; Habituation; StartleThe startle reflex is a contraction of the skeletal and facial musculature in response to a sudden intense stimulus, such as a loud noise. In humans, the eyeblink component of the startle reflex is measured using electromyography of the orbicularis oculi muscle. In rodents, a stabilimeter is used to register a whole-body flinch re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

13
57
5
1

Year Published

2001
2001
2016
2016

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 95 publications
(76 citation statements)
references
References 48 publications
13
57
5
1
Order By: Relevance
“…The notion that the detrimental effects of imipramine on PPI in our previous study (Hammer et al, 2007) were due to an increased noradrenergic activity would be consistent with the results from other studies in which noradrenaline was found to reduce human PPI (Oranje et al, 2004;Quednow et al, 2004), although a possible anticholinergic effect cannot be ruled out, as imipramine has affinity for this receptor too. The discrepancy between the current study and the studies of Liechti et al (2001) and Vollenweider et al (1999), in which MDMA (or 'ecstasy,' which is a serotonin releasing agent with similar effects on the dopaminergic and noradrenergic system) was found to increase PPI in healthy volunteers, might be attributable to the additional effects of MDMA on the dopaminergic and/or noradrenergic system.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…The notion that the detrimental effects of imipramine on PPI in our previous study (Hammer et al, 2007) were due to an increased noradrenergic activity would be consistent with the results from other studies in which noradrenaline was found to reduce human PPI (Oranje et al, 2004;Quednow et al, 2004), although a possible anticholinergic effect cannot be ruled out, as imipramine has affinity for this receptor too. The discrepancy between the current study and the studies of Liechti et al (2001) and Vollenweider et al (1999), in which MDMA (or 'ecstasy,' which is a serotonin releasing agent with similar effects on the dopaminergic and noradrenergic system) was found to increase PPI in healthy volunteers, might be attributable to the additional effects of MDMA on the dopaminergic and/or noradrenergic system.…”
Section: Discussioncontrasting
confidence: 99%
“…In a longitudinal study, Quednow et al (2004) found that the SSRI sertraline reduced habituation in patients with major depression, which is consistent with the results of the current study. Liechti et al (2001) found ketanserin to increase habituation, which is well in line with our findings, as the compound is a 5HTa/c antagonist, so an opposite effect of escitalopram is plausible. In contrast, Liechti et al (2001) found no effect of citalopram (SSRI) on habituation, probably owing to the fact that habituation was calculated as the decrement of mean startle amplitude from block 1 to 3, whereby the habituation deficits observed in the current study (over the first four trials) would have been masked.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations